2009
DOI: 10.1016/j.enpol.2009.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Oil prices and the South African economy: A macro–meso–micro analysis

Abstract: Three levels of analysis are used to track the channels by which South Africa and its people are impacted by an increase of oil prices, namely the macro-economic level, the meso-economic level and the micro-economic/household level. The paper uses an economy and energy integrated approach to quantify these different channels. The approach combines a household survey dataset and an input-output dataset to implement the models. Results indicate that the impacts on the macroeconomy are negative, with gross domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 4 publications
0
19
0
3
Order By: Relevance
“…60 An MS-IO study examined the distributional impact of increased oil prices in South Africa. 61 An increase in heating fuels is shown to be regressive and affects the poor most severely. Increased prices in transportation fuels affect higher income groups and have less regressive effects.…”
Section: Detailed Results For Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 An MS-IO study examined the distributional impact of increased oil prices in South Africa. 61 An increase in heating fuels is shown to be regressive and affects the poor most severely. Increased prices in transportation fuels affect higher income groups and have less regressive effects.…”
Section: Detailed Results For Developing Countriesmentioning
confidence: 99%
“…If fuels used for space heating are taxed, this will usually result in considerable negative distributional effects. 61,62 Similar to the case of developed countries, taxation of fuels used for transportation show less negative distributional effects. A study from Costa-Rica found that distributional effects of transportation fuels might even differ dependent on which fuel is taxed.…”
Section: The Case Of Emerging Economies and Developing Countriesmentioning
confidence: 99%
“…Fofana, Mabugu and Chitiga (2007;2008) find that oil price increases have a negative impact on the South African economy given its dependency on imported oil. Nkomo (2006a;2006b), establishes that oil price shocks tend to increase the total import bill for a country, largely because of the huge increase in the cost of oil and petroleum products.…”
Section: Introductionmentioning
confidence: 99%
“…Bellamy (2006) also attempted a similar study using a VAR framework and he …nds that the gold price played a signi…cant role in controlling the negative e¤ects from increasing oil prices. Furthermore, Fofana, et al (2007;2008), Nkomo (2006a2006b), andWakeford (2006) also analysed the South African economy and they contend that rising oil prices adversely impact on country's economic performance through various activities such as a surge in total import bill, contraction in exports, acceleration in in ‡ation and domestic interest rates.…”
mentioning
confidence: 99%